Citizen’s interaction, perceived benefits, and effectiveness of open government data on trust in government - Astuti, Hanim; Hinnant, Charles (Conference on Digital Government Research, 2025)
The declining trend of trust in government has received significant attention among scholars in various fields, particularly in efforts to find ways to reverse this decline. This paper investigates the relationship between trust in government and open government data (OGD), through a proposed model that links trust in government and three variables, i.e., citizens’ interaction with OGD, citizens perceived benefits of OGD, and perceived effectiveness of OGD. Utilizing the dataset from Pew Research Center’s survey on public perceptions of OGD, we test the model using structural equation modeling (SEM). Our findings show that the three variables positively affect trust in government. However, while the three variables are significant, perceived benefits and effectiveness of open government data are more essential determinants of trust than citizens interaction with government data. This study contributes to understanding how open government data initiatives could increase trust in government, by suggesting practical implications. Nevertheless, this study uses 2014 dataset that might not be able to capture changes in society, such political, economic, social, and technological conditions.